The Formation of High-Mass Stars: from High-Mass Clumps to Accretion Discs and Molecular Outflows - Navarete, Felipe Donizeti Teston (2018)
High-mass stars play a significant role in the evolution of the Universe and the process that leads to the formation of such objects is still an open question in Astrophysics. The details of the structures connected to the central sources, such as the circumstellar disks and the morphology of the jets at their launching points, still lack of observational evidence. In this thesis, the high-mass star forming process is investigated in terms of the evolution of high-mass clumps selected from the ATLASGAL survey based on their CO emission in the sub-millimetre. While single-dish sub-millimetre observations provide a large-scale view of the high-mass star formation process, higher angular resolution observations are required to disentangle the details of the protostars within the clumps. For this, three-dimensional infrared spectroscopy was obtained for a group of RMS sources to characterise the circumstellar environment of high-mass YSOs in linear scales of ~100-1000 AU. The ATLASGAL TOP100 sample offers a unique opportunity to analyse a statistically complete sample of high-mass clumps at different evolutionary stages. APEX data of three rotational J transitions of the CO (the CO(4-3), CO(6-5) and CO(7-6)) were used to characterise the properties of their warm gas (~155 K) content and to derive the relations between the CO and the clump properties. The CO line luminosities were derived and the analysis indicated that the CO emission increases as a function of the evolutionary stage of the clumps (from infrared-weak to HII regions) and as a function of the bolometric luminosity and mass of the sources. The comparison of the TOP100 with low-mass objects observed in the CO(6-5) and CO(7-6), together with CO(10-9) data observed for a complementary sample of objects indicated that the dependency of the CO luminosity with the bolometric luminosity of the sources gets steeper towards higher-J transitions. Although the CO luminosity of more luminous clumps are systematically larger than the values obtained for the less luminous sources, the individual analysis of each subsample suggests a similar dependency of the CO luminosity versus the bolometric luminosity for each luminosity regime. Finally, the presence of high-velocity CO emission observed for the TOP100 suggests that ~85% of the sources are driving molecular outflows. The selection of isolated high-mass objects undergoing mass accretion is fundamental to investigate if these objects are formed through an accretion disc or if they are formed by merging of low-mass YSOs. The near-infrared window provides one of the best opportunities to investigate the interior of the sub-mm clumps and study in details their individual members. Thanks to the relatively high-resolution obtained in the K-band and the moderate reddening effects in the K-band, a sample of eight (8) HMYSOs exhibiting large-scale H2 outflows were selected to follow-up K-band spectroscopic observations using the NIFS spectrometer (Gemini North). All sources exhibit extended continuum emission and exhibit atomic and molecular transitions typical of embedded objects, such as Brackett-gama, H2 and the CO lines. The H2 lines are tracing the launching point of the large-scale jets in scales of ~100 AU in five of eight sources (63%). The identification of jets at such small scales indicates that these objects are still undergoing mass accretion. The Brackett-gama emission probes the ionised gas around the HMYSOs. The analysis of the Brackett-gama spectro-astrometry at sub-pixel scales suggests that the line arises from the cavity of the outflows or from rotating structures perpendicular to the H2 jets (i.e., disc). Five sources also exhibit CO emission features (63%), and three HMYSOs display CO absorption features (38%), indicating that they are likely associated with circumstellar discs. By further investigating the kinematics of the spatially resolved CO absorption features, the Keplerian mass of three sources was estimated in 5±3, 8±5 and 30±10 solar masses. These results support that high-mass stars are formed through discs, similarly as observed towards low-mass stars. The comparison between the collimation degree of the molecular jets or outflows detected in the NIFS data with their large-scale counterparts indicate that these structures present a relatively wide range of collimation degrees.